Evaluation of Protective Role of Date Palm Pollen against Cisplatin-Induced Reproductive Toxicity in Rats - Abdelrahim, Musab A. M.; Ahmed, Elhadi M. M.; Taj-Eldin, Imad M.; Mohammed, Abd-Elwahab H. (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2025)
Date palm pollen (DPP) is herbal mixture that widely used in traditional medicine to improve fertility. The current study aimed to determine the protective role of the DPP extract against cisplatin-induced reproductive toxicity in rats. Sixty rats were used (30 of each sex) and allocated to normal, negative, and test control groups of males and females (10 animals per group). Reproductive toxicity was induced by an intraperitoneal injection of cisplatin (4.5 mg/kg/72 hour) in the negative and test groups, whereas the test groups also received daily oral doses of DPP methanolic extract (250 mg/kg). At the end of the experimental period (30 days), the rats were sacrificed to determine the fertility parameters. The obtained results showed that, oral administration of DPP extracts exhibited protective effects as demonstrated by a prominent increase in serum estradiol concentration, recovery from reduction in gonads weight, and a considerable enhancement on histological observations among male and female rats. Moreover, elevation in epididymal sperm count and motility in male animals was observed compared to that in cisplatin-treated rats. DPP had a significant effect on estradiol levels, as well as protective effects against cisplatin-induced reproductive toxicity in both male and female rats. Keywords: Cisplatin, date palm, epididymal characteristics, Phoenix dactylifera